2015
DOI: 10.1007/s11746-015-2714-4
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi Method and Grey Relational Analysis to Improve in Situ Production of FAME from Sunflower and Jatropha curcas Kernels with Subcritical Solvent Mixture

Abstract: This study investigates the possibility of employing in situ (trans)esterification (ISTE) under the subcritical condition (200–250 °C) of the solvent mixture (methanol + acetic acid) with a high solid loading and a low solvent to solid ratio (SSR). The Taguchi method together with grey relational analysis was used to improve both FAME yield and productivity. It was found that temperature reaction time and SSR were factors which contributed the most in obtaining high FAME yields. In addition to the above‐mentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Since sub and supercritical may proceed with and without catalyst, (trans)esterification may well occur also within the biomass. This was observed in the subcritical ISTE study of Sutanto et al [92] where whole sunflower kernels were utilized and a mixture of FAME and unreacted AG were still found in the solid residue. Solubilization and breakdown of biomass releasing the lipids could be possible since only about 10 wt% of the initial biomass was left after the reaction [79].…”
Section: Two-step Sub or Supercritical Processmentioning
confidence: 63%
See 3 more Smart Citations
“…Since sub and supercritical may proceed with and without catalyst, (trans)esterification may well occur also within the biomass. This was observed in the subcritical ISTE study of Sutanto et al [92] where whole sunflower kernels were utilized and a mixture of FAME and unreacted AG were still found in the solid residue. Solubilization and breakdown of biomass releasing the lipids could be possible since only about 10 wt% of the initial biomass was left after the reaction [79].…”
Section: Two-step Sub or Supercritical Processmentioning
confidence: 63%
“…Solubilization and breakdown of biomass releasing the lipids could be possible since only about 10 wt% of the initial biomass was left after the reaction [79]. It was also observed that higher FAME yield was obtained from Jatropha kernels than sunflower kernels under the same reaction conditions despite the fact that Jatropha contains relatively higher lipids [92].…”
Section: Two-step Sub or Supercritical Processmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these techniques have not been widely used yet in the biodiesel production process. Techniques used in the latest studies of non‐catalytic and heterogeneous acid/base catalytic biodiesel production include artificial neural network (ANN), 151,152 response surface methodology (RSM), 63,103,151–154 and Taguchi method or orthogonal design 155–157 . Optimization studies on catalyst preparation step 158 and biodiesel properties 159 were also reported.…”
Section: Factors Affecting Non‐catalytic and Heterogeneous Solid Catamentioning
confidence: 99%